Introduction to operations management - Naylor, John; Naylor, John (Harlow : Financial Times Prentice Hall, 2002)
This text offers a comprehensive and concise introduction to operations management. Numerical models are used to illustrate decision processes, though the emphasis is rigrous, not quantitative, and there is material on supply chain management and e-commerce.
Previous ed. published as: Operations management. London : Pitman, 1996.
Includes bibliographical references and index.
oif 09/02/15
Loan
Keywords: Production management; Operations management